Museums and the Environment: a handbook for education - AMERICAN ASSOCIATION OF MUSEUMS (New York Amaerican Association of Museums, 1971)
The A.A.M presents this book and the suggsetions in it for the benefit of museums and the public they serve.
Keywords: Nature -- Effect of human beings on -- Exhibitions; Pollution -- Exhibitions; .Human ecology -- Exhibitions